Interleukin‐33 exacerbates allergic bronchoconstriction in the mice via activation of mast cells. Issue 5 (24th February 2015) - Sjöberg, L. C.; Gregory, J. A.; Dahlén, S.‐E.; Nilsson, G. P.; Adner, M.
Abstract Background Interleukin‐33 (IL‐33) is implicated as an epithelium‐derived danger signal promoting Th2‐dependent responses in asthma. We hypothesized that IL‐33 might also have direct effects on mast cell‐driven allergic airway obstruction. Methods The effects of IL‐33 on allergic responses in the airways of sensiti‐zed mice were assessed both in vivo and ex vivo, as well as on cultured mast cells in vitro. Results In vivo, the allergen‐induced increase in resistance in the conducting airways was enhanced in mice pretreated with IL‐33. Also, in the isolated airways, the allergen‐induced contractions were increased in preparations from animals subjected to intranasal IL‐33 pretreatment. These effects in vivo and ex vivo were blocked by the 5‐HT2A receptor antagonist ketanserin and absent in mice without mast cells. Likewise, the IL‐33‐induced enhancement of the allergen response was absent in isolated airways from mice lacking the IL‐33 receptor. Moreover, exposure to IL‐33 increased secretion of serotonin from allergen‐challenged isolated airways. In cultured mast cells, IL‐33 enhanced the expression of tryptophan hydroxylase 1, serotonin synthesis, and storage, as well as the secretion of serotonin following IgE receptor cross‐linking. Conclusion These results demonstrate that IL‐33 exacerbates allergic bronchoconstriction by increasing synthesis, storage, and secretion of serotonin from the mast cell. This mechanism has implications for the development of airway obstruction in asthma.